The tale of three trees : a traditional folktale - Hunt, Angela Elwell, 1957- (Lion Pub. Corp., 1989)
This retelling of a popular folk tale is suitable for any time of the year, but has particular links to Christmas and Easter. It tells of the hopes and dreams of the three little trees.